An evaluation of the present guidance program and a proposed guidance program for Baliuag Colleges and the use of career materials in vocational counseling for Baliuag Colleges - Buensuceso, Aurora L. Almonte (Animo Repository, 1974)
The first part of this study aims to evaluate the present guidance program of the Baliuag Colleges and to propose a program that will answer the needs of the students. Evaluation of the existing guidance program was done by means of a checklist through the normative survey method. There were 500 respondents made up of the following groups : 200 high school students, 240 college students , and 60 others, composed of the guidance staff members, faculty, and administrators combined. It was found that the existing guidance program was weak in counseling, pupil inventory, placement, and group guidance services. General and specific objectives were set up to make the proposed program functional in meeting the needs of the students and the faculty. The services proposed in the guidance program were individual inventory, information, counseling, orientation, testing, placement, and follow-up services. The second part of this study seeks to to answer the following questions : 1) Is there a need for career materials in vocational counseling in Baliuag Colleges? 2) What program of activities can be set up to implement vocational counseling? 3) Why is there a need for students in Baliuag Colleges to know employment opportunities offered by the construction industry? and 4) What levels of jobs and requirements for each educational level are offered by the construction industry? A prepared questionnaire devised by the Career Materials Development Project (CMDP) based at De La Salle College was used in the interviews conducted with personnel managers, supervisors, foremen, and employees. Three companies supplied the necessary data used for the industrial monograph prepared - the Atlantic Gulf and Pacific Company (AG & P), the William Golangco Construction Corporation (WGCC), and the Salili and Partners (SAP). The interview data were integrated in order to get a representative picture of career opportunities in the construction industry.